GUIDELINES FOR PREPARATION OF MANUS THERAPEUTIC FOR THAI TRADITIONAL MEDICINE STUDENTS - Wiriya, Suthida; Punfa, Wanisa; Tansuwanwong, Siwapong; Taoprasert, Kanyanoot; Taoprasert, Yingyong (Journal of Educational Review Faculty of Education in MCU, 2021)
The purposes of this research article were of this study is to create a guideline for body and mind preparation process for Thai traditional medicine students before manus therapeutic. Related documents, textbooks and research in Thai traditional medicine, Chinese medicine, modern medicine, and sports science were investigated for using as a guideline in developing the hand preparation process for Thai traditional medicine students. The results showed that the hand preparation process needed 3 requirements, namely: 1) the preparation of mental readiness to be mindfulness and respectfulness to the master, 2) the preparation of hand hygiene, before and after treating patients by washing hands with soap or alcohol in 7 steps to reduce contamination and spread germs, and 3) the preparation of hand strength for practicing by using hands to resist against an object in the form of grip or contracting the muscles for a period of time from a light weight to heavy weight. In conclusion, a guideline for treatment preparation of disease can proceed to further developed into a readiness manual for Thai traditional medicine students before manus therapeutics.